When Good Things Turn Bad: Evidence from G-7 Serial Acquirer Bidding - Ibrahim Yousef (Asian Academy of Management Journal of Accounting and Finance, 2020)
This study investigates the impact of acquirer bidding experience on acquiring abnormal returns based on empirical evidence from a large sample of 10,880 bidders making 23,852 deals from G-7 countries. Both event study and regressions analysis have been used to examine the impact of acquirer bidding experience on acquirer returns. The findings show that “single acquirers” achieve higher returns, with a cumulative average abnormal return (CAAR) of 3.354%, but this number tends to decrease with increasing numbers of previous bids. In addition, the results of the bivariate analysis demonstrate that a single acquisition alone generates greater abnormal returns than those which are part of a series of acquisitions, with very robust results even after accounting for additional heterogeneity in payment method, target status and country/industry diversification. The findings of the multivariate analysis also confirm that serial acquirers are associated with significantly lower abnormal returns. This evidence conflicts with the notion that more experience with mergers and acquisitions (M&As) will correspond to improve target valuation and thus lead to more profitable agreements. In contrast, my findings imply that shareholder wealth is destroyed by serial acquirers, which suggests that the goal of maximising firm value is not always the sole motivation for engaging in M&A activities.